Alice in Wonderland - Loehr, Mallory; Tenniel, John, Sir, 1820-1914; Carroll, Lewis, 1832-1898. (New York : Random House, 2009)
A shortened, simplified version of the tale in which a little girl falls down a rabbit hole and discovers a world of nonsensical and amusing characters.
3.3
3-6
Keywords: Girls -- Juvenile fiction; Rabbits -- Juvenile fiction; Girls -- Fiction; Rabbits -- Fiction; Fantasy; Girls -- Fiction; Rabbits -- Fiction; Fantasy fiction; Fantasy fiction; Readers (Elementary)